2012
DOI: 10.3945/jn.111.156448
|View full text |Cite
|
Sign up to set email alerts
|

Summary of an NIH Workshop to Identify Research Needs to Improve the Monitoring of Iodine Status in the United States and to Inform the DRI

Abstract: The Office of Dietary Supplements (ODS) at the NIH sponsored a workshop on May 12-13, 2011, to bring together representatives from various NIH institutes and centers as a first step in developing an NIH iodine research initiative. The workshop also provided an opportunity to identify research needs that would inform the dietary reference intakes for iodine, which were last revised in 2001. Iodine is required throughout the life cycle, but pregnant women and infants are the populations most at risk of deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…Iodine is ingested from a variety of sources and its intake is currently assessed by urinary concentration. Urinary iodine values of 100-199 lg/L (150-249 in pregnancy) are considered indicative of adequate iodine intake (32). There are no U.S. population data on urinary iodine before 1970, but landmark studies by David Marine during the World War I period showed a high prevalence of goiter in the Great Lakes area and the serious consequences of iodine deficiency (33,34), marking de facto the beginning of iodine supplementation in this country.…”
Section: Discussionmentioning
confidence: 98%
“…Iodine is ingested from a variety of sources and its intake is currently assessed by urinary concentration. Urinary iodine values of 100-199 lg/L (150-249 in pregnancy) are considered indicative of adequate iodine intake (32). There are no U.S. population data on urinary iodine before 1970, but landmark studies by David Marine during the World War I period showed a high prevalence of goiter in the Great Lakes area and the serious consequences of iodine deficiency (33,34), marking de facto the beginning of iodine supplementation in this country.…”
Section: Discussionmentioning
confidence: 98%
“…30 The IOM recommends an iodine intake from dietary and supplement sources of 150 mcg per day pre-conception, and 220 mcg per day for pregnant women. 31 …”
Section: Vitamin Dmentioning
confidence: 99%
“…In contrast, high thyroid volume is an indicator of longterm iodine deficiency that may persist for years after iodine repletion (Zimmermann et al, 2006). Serum thyroglobulin (Tg), a thyroid protein that facilitates the uptake and storage of iodine in the thyroid gland, has been proposed as a biomarker of intermediate-term population iodine nutrition status (weeks to months) based on associations with UIC (Knudsen et al, 2001;Krejbjerg et al, 2016;Swanson et al, 2012;Vejbjerg et al, 2009), and sensitivity to changes in iodine status following iodine supplementation (Gordon et al, 2009;Ma and Skeaff, 2014;Skeaff and Lonsdale-Cooper, 2013;Vejbjerg et al, 2009;Zimmermann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%